PROFIL ANALISIS BATU SALURAN KENCING DI INSTALASI LABORATORIUM KLINIK RSUP SANGLAH DENPASAR - Rasmika Dewi, Dewa Ayu Putu; Ngurah Subawa, Anak Agung (journal of internal medicine; Vol. 8, No. 3 September 2007)
Urolithiasis is a pathological condition that is caused by the formation of hard mass like stone along the urinary tract. Identification of the urinary stones can be done through chemical analysis or using of infrared spectroscopy. The semiquantitative methods used to analyze are titrimetric and colorimetric. This study was cross sectional whose results were descriptive. The data used in this study was 113 urinary stone analysis records taken from Routine Clinic of Laboratory Clinic Installation at Sanglah Hospital in period January until December 2007 (one year). The prevalence of urolithiasis in males were more than females (4:1) and it was mostly occur in age range 40-60 years old of both sexes. Generally, more than one kind of stone compositions were found in a patient of urolithiasis, the dominant was calcium oxalate.
Keywords: urolithiasis, titrimetric, colorimetric, calcium oxalate.